Longer length of post-acute care stay causes greater functional improvements in poststroke patients. Issue 26 (2nd July 2021) - Tung, Yu-Ju; Huang, Chin-Tsan; Lin, Wen-Chih; Cheng, Hsin-Han; Chow, Julie Chi; Ho, Chung-Han; Chou, Willy
Abstract : Abstract: Post-acute care (PAC) is a type of transitional care for poststroke patients after the acute medical stage; it offers a relatively intensive rehabilitative program. Under Taiwan's National Health Insurance guidelines, the only patients who can transfer to PAC institutions are those who have had an acute stroke in the previous month, are in a relatively stable medical condition, and have the potential for improvement after aggressive rehabilitation. Poststroke patients receive physical, occupational, and speech therapy in PAC facility. However, few studies have evaluated the effects of PAC in poststroke patients since PAC's initiation in Taiwan. Thus, this study aims to investigate whether the length of stay in a PAC institution correlates with patients' improvements. This retrospective and single-center study in Taiwan enrolled 193 poststroke patients who had received acute care at Chi-Mei Medical Center, Taiwan, at any period between 2014 and 2017. Data on their length of stay in the PAC institution were collected. Poststroke patients' functional ability—such as activities of daily living (ADL) function and swallowing ability—as well as their corresponding scales were assessed on the first and last day of PAC stay. Statistical analysis was conducted by SPSS version 21.0 . The average duration of PAC stay was 35.01 ± 16.373 days. Duration of PAC stay was significantly positively correlated with the Barthel index ( P  < .001), Berg balance test score ( P  < .001), gait speed ( P  = .002), and upper sensory function and upper motor function within the Fugl–Meyer Assessment (both P  < .001). Poststroke patients with longer stay in a PAC institution had superior ADL function, balance and coordination, walking speed, and upper-limb dexterity and sensory function.